การวิเคราะห์ภาวะผู้นำทางวิชาการของผู้บริหารโรงเรียนพระปริยัติธรรม แผนกสามัญศึกษา - พิทยา จันทร์วงษ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
The objectives of this study aimed to 1) analyze the instructional leadership factors of administrators, 2) study the level of actual performance regarding factors of administrators according to the opinions of administrators and teachers, and 3) compare the level of actual performance regarding factors. Interviewing with 20 experts was conducted to analyze and identify the factors. Data were analyzed by frequency, percentage, and content analysis. Questionnaires were used to collect the quantitative data in order to study the level of actual performance regarding factors. The data were given by 2 groups of sample population comprising 164 administrators and 305 teachers, and were analyzed by mean and standard deviation. And t-test was used to compare the level of actual performance regarding factors of administrators. The research results were as follows: 1. The instructional leadership factors consisted of 3 factors and 15 behaviors: 1) to define the school mission containing 2 behaviors; 2) to manage the curriculum and instructional programs having 5 behaviors; and 3) the characteristics of instructional leadership and to promote school climate with 8 behaviors. 2. In general, the level of actual performance regarding factors, as perceived by administrators and teachers, was at a high level. 3. When comparing the actual performance regarding factors, it turned out that the general mean difference fell at a significance level of .05. While considering each factor, the first factor had no mean difference, but the second and the third factors had mean difference at a significance level of .05.